The home-made organic ecology pesticides / Nur Hamizah Syahirah Ruhizat ... [et al.] - Ruhizat, Nur Hamizah Syahirah; Hairulnizam, Muhammad Haikal; Badrul Shahir, Nur Farisha Amira; Zubair, Mohamad Haq Iskandar (2020)
The increases of chemical pesticides usage for farmer or gardeners to protect their plant is a continuous concern for people and our lovely environment. The purpose of this study to avoid the toxicity chemical pesticides to human and to air pollution from happen. It is because inside the common pesticides that commercial, there is chemical ingredients that using. These chemical pesticides can be dangerous and hazardous to human when they did not work in the right manner. Besides, can also cause air and water pollution when using uncontrolled. Worrying about nowadays situation, our group got the idea to use only organic ingredients to overcome the using of chemical pesticides. All we used are chillies, gingers, and lemongrass. This amazing home-made ecology pesticide is so smelly and can make the insects fly and go away. The organic insect poison is found to play the greatest role in fighting the concern of people about the commercialized chemical pesticides. A trial was carried out in four weeks when we try to test it on several types of plants. Surprisingly that the result shows a great positive impact because the tested plants are such in a good condition and did not be destroyed by any parasite insect and also free from any chemical. Unbelievable too, the leaves also showed the more greenly look and healthy.